2010
DOI: 10.1177/1934578x1000501005
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Bisnor-clerodane Diterpenoid from Polyalthia Simiarum

Abstract: The stem bark of Polyalthia simiarum has yielded a new bisnor-type clerodane diterpenoid, 2-oxo-14,15-bisnor-3,11Ekolavadien-13-one (1), and three previously known clerodane derivatives, kolavenic acid (2), 16β-hydroxycleroda-3,13(14)Zdien-15,16-olide (3), and 16-oxocleroda-3,13(14)E-dien-15-oic acid (4). The structures of these compounds were unambiguously determined by extensive NMR studies as well as by comparison with related compounds. Till now this is the second report of the occurrence of any unusual C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Plant extracts and natural products are sources of anti-oxidative agents. As reported (Figure 2), flavonoids (61)(62)(63) [54,55] and proanthocyanidins [56] extracted from P. longifolia leaves and clerodane diterpenes (47) isolated from stem bark of P. simiarum [57] as well as stem bark of P. longifolia extracts [58] displayed anti-oxidative activities, as detected by the DPPH method and enzymatic activity assay. Oyeyemi et al (2020) demonstrated that P. longifolia aqueous and methanolic leaf extracts present the prophylactic and the curative activities against cadmium (a major environmental pollutant)-induced hepatotoxicity by relieving the oxidative stress in rats [59].…”
Section: Anti-oxidant Phytochemicals In Polyalthiasupporting
confidence: 57%
“…Plant extracts and natural products are sources of anti-oxidative agents. As reported (Figure 2), flavonoids (61)(62)(63) [54,55] and proanthocyanidins [56] extracted from P. longifolia leaves and clerodane diterpenes (47) isolated from stem bark of P. simiarum [57] as well as stem bark of P. longifolia extracts [58] displayed anti-oxidative activities, as detected by the DPPH method and enzymatic activity assay. Oyeyemi et al (2020) demonstrated that P. longifolia aqueous and methanolic leaf extracts present the prophylactic and the curative activities against cadmium (a major environmental pollutant)-induced hepatotoxicity by relieving the oxidative stress in rats [59].…”
Section: Anti-oxidant Phytochemicals In Polyalthiasupporting
confidence: 57%
“…163 Isolated from several different plant species, compounds 1086–1089 are unusual 14,15-bisnor clerodanes with a C-4/C-5 double bond, 44,79,219,391 and compounds 1090–1096 are 13,14,15,16-tetranor-clerodanes. Among the latter tetranor-clerodanes, C-12 is present as a free carboxylic acid ( e.g.…”
Section: Structure Classifications and Sources Of Clerodane Diterpmentioning
confidence: 99%
“…Polyalthia species have a wide distribution since they were found in Asia, Africa, Australia, and New Zealand [1] . The plants of this genus have been considered as a medicinally important resource because they have bioactive compounds type clerodane diterpenoids [2–4] . Polyalthia plants are also a rich reservoir of antimicrobial essential oils [5–7] .…”
Section: Introductionmentioning
confidence: 99%